2020
DOI: 10.3390/s20247179
|View full text |Cite
|
Sign up to set email alerts
|

IMU-Based Movement Trajectory Heatmaps for Human Activity Recognition

Abstract: Recent trends in ubiquitous computing have led to a proliferation of studies that focus on human activity recognition (HAR) utilizing inertial sensor data that consist of acceleration, orientation and angular velocity. However, the performances of such approaches are limited by the amount of annotated training data, especially in fields where annotating data is highly time-consuming and requires specialized professionals, such as in healthcare. In image classification, this limitation has been mitigated by pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The findings ( Figure 2 ) revealed that 54 articles used motion tracking data in health care and physical wellness applications, of which 42 (78%) articles used motion-tracking sensors [ 75 - 81 , 84 - 86 , 88 - 97 , 101 , 103 - 116 , 119 , 121 - 123 , 125 , 126 ]. Overall, 70% (38/54) of the articles used AI technology combined with motion tracking data [ 75 , 77 , 79 , 82 - 85 , 87 , 89 - 91 , 93 , 94 , 97 , 99 - 101 , 103 , 105 , 106 , 108 , 109 , 111 - 113 , 117 - 128 ]. The role of AI mainly functions for data classification, monitoring, and visualization among the included studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings ( Figure 2 ) revealed that 54 articles used motion tracking data in health care and physical wellness applications, of which 42 (78%) articles used motion-tracking sensors [ 75 - 81 , 84 - 86 , 88 - 97 , 101 , 103 - 116 , 119 , 121 - 123 , 125 , 126 ]. Overall, 70% (38/54) of the articles used AI technology combined with motion tracking data [ 75 , 77 , 79 , 82 - 85 , 87 , 89 - 91 , 93 , 94 , 97 , 99 - 101 , 103 , 105 , 106 , 108 , 109 , 111 - 113 , 117 - 128 ]. The role of AI mainly functions for data classification, monitoring, and visualization among the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…The studies that involved placing sensors on the full body and in environments were widely reported [ 84 , 94 , 96 , 103 , 109 - 112 , 115 , 116 , 119 , 122 , 123 ], and the purposes of using full-body motion tracking are commonly argued for analyzing specific movements or securing the credibility of system evaluations [ 94 , 106 , 110 , 112 , 115 , 116 , 123 ]. The investigations involving the placement of sensors in physical spaces mostly use motion capture and image processing techniques [ 117 , 119 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recent results have shown that IMUs and machine learning classifiers are very effective in identifying activities in healthy controls [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. The accuracies often rely on the number of IMUs used and their location, with the wrist, chest, ankle, and thigh commonly used.…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to technological advances, inertial measurement units (IMUs) are available in small sizes, at low cost, and are widely used for biomedical applications such as gait analysis [ 1 ], rehabilitation [ 2 ], sports [ 3 , 4 , 5 ], injury prevention [ 6 , 7 ], and activity monitoring [ 8 ]. In general, the data from single or multiple IMUs placed on body segments are fused to obtain spatiotemporal parameters [ 9 ] or joint orientation [ 10 ] during movement.…”
Section: Introductionmentioning
confidence: 99%